Research of Composed Profile with Wide Top High-sealing Zone of Involute Rotor - Yulong Li; Ping Liu; Yong Zang; Jun Fan; Ying Cheng (Jixie chuandong)
To realize the higher performance design of involute rotor, based on four possible top structure, from seven aspects of profiles parameterization, the limit value of shape coefficient, volume utilization coefficient, size optimization and so on, the higher performance profiles with wide top for high-sealing zone is finally constructed. Then, from lightweight of rotor as design object, the optimization model is constructed. Finally, an innovative configuration of profiles is given to eliminate trapped-gas phenomenon. All results show that the innovative profiles is meet high performance requirement for maximizing volume utilization coefficient and minimizing radial top leakage. The trapping-gas phenomenon is eliminated better by the new avoid-arc, which is easy machined. The shape coefficient or volume utilization and top half angle have approximately negative linear correlation, etc. It is concluded that the full parametric modeling and design method can be used for other rotor profiles with radial high-sealing zone.